Management treasure: contributions to accountability in public management (Research, Society and Development, 2020)
Society has demanded public management models that are more efficient, effective and effective, but with transparency in its actions and accountability. This is where the importance of public financial administration and its management tools is revealed so that the federal government can work on accountability in public management. This paper theoretically analyzes the tools used by SIAFI, SIAFI WEB and Managerial Treasury. For this, we proceed to a comparative and purposeful analysis against the advantages and disadvantages of the tools in use. It can be seen that the Management Treasury can contribute in order to remedy the identified gap, as well as optimizing for public management to effectively achieve accountability.